Subliminal Word Processing: EEG Detects Word Processing Below Conscious Awareness - Samuil Pavlevchev; Minah Chang; Alessandra Natascha Flöck; Peter Walla (Brain Sciences, 2022)
The present electroencephalography (EEG) study observed how the brain processes visual stimuli (words and shapes) displayed with four different duration times (17 ms, 33 ms, 67 ms, and 100 ms). All stimuli had to be classified into “I saw nothing”, “I saw a blur”, “I saw a word,” or “I saw a shape” via distinct button presses while brain potentials were being measured. The neurophysiological correlates of word and shape processing were subsequently analysed and compared for two distinct time points at the occipito-parietal area in both hemispheres (P7 and P8). In a further step, word and shape identification rates were also analysed. Identification rates revealed that participants recognized words and shapes when presented for 17 ms at a rate of only 6% and 7%, which is poor enough to assume an overall lack of conscious recognition. Analysis of EEG data revealed two time points of interest, one at 210 ms and the other at 280 ms post stimulus onset. Brain potentials at the earlier time point reflect modulations in presentation duration with increased amplitudes elicited by longer presentations. At this time point, no differences were seen between words and shapes in both hemispheres. The later time point, though, clearly distinguished between word and shape processing with totally missing amplitudes (i.e., brain activity) in the case of shapes in general in both hemispheres. Crucially, words presented for only 17 ms still elicited an average brain potential amplitude significantly different from the corresponding 17 ms presentations of shapes at this time point at electrode location P7, even though both stimuli categories were basically not seen (i.e., not consciously recognized). This later word-specific brain potential for the shortest presentation duration is interpreted as neurophysiological evidence of subliminal word processing. Strikingly, this difference was not found in the right hemisphere at P8.